2013
DOI: 10.1111/php.12066
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed, UVC‐Induced, Sequence‐Dependent DNA Damage Detection

Abstract: The exposure of DNA to ultraviolet (UV) radiation causes sequence-dependent damage. Thus, there is a need for an analytical technique that can detect damage in large numbers of DNA sequences simultaneously. In this study, we have designed an assay for UVC-induced DNA damage in multiple oligonucleotides simultaneously by using a 96-well plate and a novel automated sample mover. The UVC-induced DNA damage is measured using smart probes, analogs of molecular beacons in which guanosine nucleotides act as the fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…S4†). Therefore, the encapsulated yeast cells are cultivated in fresh liquid media and in normal solution (without fresh medium) under short wave ultraviolet radiation (UVC, strongest ultraviolet band of sunlight for destroying genetic structure of cells 34 ) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…S4†). Therefore, the encapsulated yeast cells are cultivated in fresh liquid media and in normal solution (without fresh medium) under short wave ultraviolet radiation (UVC, strongest ultraviolet band of sunlight for destroying genetic structure of cells 34 ) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The overall thermal transition profile of the SP alone is sigmoidal, which is consistent with the thermal transition behavior of a typical MB or SP. 31,32,35,36 From this profile, the T m of the SP was determined to be 63 C. This T m depends on the length of its stem hybrid and the G-C content of the stem. 31 The stem of the SP consists of eight residues, five of which are G-C, excluding the three G-overhangs that are flanking the fluorophore as quenchers (Fig.…”
Section: Thermal Transition Profilesmentioning
confidence: 99%
“…26,33,34 The SP recognizes its complementary target sequence by switching on its fluorescence, which turns off in the absence of the target sequence. Due to their excellent signaling property, SP has been successfully used for various detection assays, including detection of ultraviolet (UV)-induced DNA photodamage, 35,36 real-time monitoring of the activity and kinetics of T4 polynucleotide kinase, 37 detection of ATP, 38 monitoring of DNA methyltransferase activity, 39 and monitoring of DNA polymerase fidelity, 40 among others. These studies showed the inherent sensitivity of SP and demonstrated that they are capable of recognizing even single-base mismatches.…”
Section: Introductionmentioning
confidence: 99%
“…If a nucleic acid sequence has a single-base mutation in it, the SP can differentiate between this mismatch and the target sequence by providing a relatively lower fluorescence signal compared to that of the perfect target, which indicates a less stable hybrid between the SP and the mismatch sequence. This exquisite signaling property makes SPs effective analytical tools in various applications, such as monitoring polymerase chain reactions (PCR), DNA polymerase fidelity, T4 polynucleotide kinase activity, adenosine triphosphate (ATP) detection, detection of UV-induced nucleic acid photodamage, genetic testing, and biomedical diagnostics [8,9,10,11,12,13]. SPs are structurally similar to molecular beacons (MBs), except that guanine bases are used in SPs to replace an extrinsic quencher label used in MBs.…”
Section: Introductionmentioning
confidence: 99%